2012
DOI: 10.1093/jmt/49.2.150
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Preference, Familiarity and Psychophysical Properties in Defining Relaxation Music

Abstract: Results from this study provided an in-depth operational definition of the intrinsic parameters in relaxation music and also highlighted the importance of preference and familiarity in eliciting the relaxation response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 0 publications
3
48
0
3
Order By: Relevance
“…Similar to other musical valences, relaxation is enhanced when participants choose the music themselves (Tan et al, 2012).…”
mentioning
confidence: 95%
“…Similar to other musical valences, relaxation is enhanced when participants choose the music themselves (Tan et al, 2012).…”
mentioning
confidence: 95%
“…Cooper and Foster (2008) used various genres of music to aid patients'levels of relaxation in a radiotherapy waiting room and found that enjoyment of the music was associated with increased relaxation. Additionally, Tan et al (2012) found that there was a significant positive correlation between music preference and the degree of relaxation in music therapists and adult participants.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Patients' preferences and familiarity levels with music used in waiting periods may impact their anxiety levels and should be considered (Tan, Yowler, Super, &Fratianne, 2012). The rationale behind music selection is an important decision to articulate in future research on this topic (Cooke et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this, it has been proposed that the ANS system could serve as the mechanism by which music can apply its effects on humans. 3,4 Music has long been associated with relaxation 5 and has spawned an entire professional field of music therapy with distinct certification and academic literature. 6 It is speculated that the auditory neural impulses respond in unique ways to the sound wave frequency, amplitude, and timbre of music.…”
Section: Introductionmentioning
confidence: 99%